A study of left ventricular diastolic dysfunction in patients of sickle cell disease - Shah, Mohita; Kothari, Prafful (International Journal of Advances in Medicine, 2022)
Background: Left ventricular diastolic filling patterns are altered in patients with sickle cell anaemia and these diastolic abnormalities may be present in the absence of heart failure. These abnormal patterns suggest an intrinsic myocardial abnormality in patients with sickle cell anaemia and may prove to be early markers of cardiac disease. The ventricles do not properly relax and become stiff meaning they cannot fill with blood properly. Methods: This study was carried out in tertiary health care hospital in western India, where homozygous sickle cell disease patients and age and haemoglobin matched controls were taken into cross sectional observational study design. Results: The mean values of E, A, E/A, IVRT, DT, AT, were in normal range in controls. In cases although the mean values of E, A, E/A, IVRT, DT, AT were in normal range, there were 19 cases of sickle cell anaemia who had significant alteration in indices of diastolic LV function from normal range. Out of these 20 cases with diastolic dysfunction, 11 cases had significant increase in (E) velocity from normal range with E/A ratio more than 2 suggestive of restrictive filling pattern of diastolic dysfunction while in 8 cases E value was less than normal with increase in (A) velocity and E/A ratio was less than 1 suggestive of impaired relaxation pattern of diastolic dysfunction. When indices of diastolic LV function were compared in cases and controls, mean early peak filling velocity (E) was significantly higher in cases. Conclusions: In present study, out of 37 cases 19 (51%) cases had LV diastolic dysfunction. Of these 19 cases with diastolic dysfunction, 11 cases had restrictive filling pattern and 8 cases had impaired relaxation pattern of diastolic dysfunction.